Prevalence of bacteria involved in bovine respiratory disease in dairy heifers in Spain: influence of environmental factors - Barroso-Arévalo, Sandra; Re, Michela; Ayanz, José María San Miguel; Val, Eugenia Peralta; Alvarado-Piqueras, Alberto; Fernández-Valeriano, Rocío; Blanco-Murcia, Javier (Frontiers in Veterinary Science, 2025)
IntroductionBovine Respiratory Disease (BRD) is a multifactorial condition and a major health and economic concern in dairy production.MethodsThis study aimed to determine the prevalence of five key bacterial pathogens—Mannheimia haemolytica, Pasteurella multocida, Trueperella pyogenes, Mycoplasma bovis, and Histophilus somni—in Spanish dairy heifers and to evaluate the influence of seasonality, geographical location, farm size, and antibiotic use. In 2017, samples (deep nasopharyngeal swabs, transtracheal aspirates, and blood) were collected from 855 heifers (<12 months old) in 50 farms across Spain. Bacterial isolation and serological testing (ELISA) were performed.ResultsMycoplasma spp. showed the highest overall prevalence (26.7% at the individual level by culture; 75.7% of cultured farms), with PCR confirming M. bovis in 89% of Mycoplasma-positive farms. Serology revealed 16.3% individual-level positivity for M. bovis and 63% farm-level positivity. T. pyogenes was also notable, detected in 6.0% of animals (45% of farms). Lower isolation rates were observed for M. haemolytica (2.5%) and P. multocida (3.5%), while H. somni was not detected. Larger farm size, winter season, and certain regions were significantly associated with higher prevalence of M. bovis and T. pyogenes.DiscussionThese findings underscore the need for improved management practices—such as better ventilation, reduced stocking density, and targeted vaccination—to mitigate BRD risk in high-prevalence settings.